2021
DOI: 10.1017/s0266462321000064
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in health technology assessment: update of a systematic review of international experiences

Abstract: Objective To summarize current evidence on patient and public involvement (PPI) in health technology assessment (HTA) in order to synthesize the barriers and facilitators, and to propose a framework to assess its impact. Methods We conducted an update of a systematic review published in 2011 considering the recent scientific literature (qualitative, quantitative, and mixed-methods studies). We searched papers published between March 2009 (end of the initial search) and December 2019 in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 54 publications
0
26
0
1
Order By: Relevance
“…The “invited spaces” for patient participation have been set by HTA policy and practice and leave significant opportunities for broadening through mutual discussions ( 22 ). Public representatives have a place on the appraisal committees in a number of countries ( 17 , 23 , 24 ) and in some healthcare systems patients are payers in addition to being the focal point of what healthcare is about. As payers, patients are legitimate stakeholders within HTA.…”
Section: Involving Patients In Htamentioning
confidence: 99%
See 1 more Smart Citation
“…The “invited spaces” for patient participation have been set by HTA policy and practice and leave significant opportunities for broadening through mutual discussions ( 22 ). Public representatives have a place on the appraisal committees in a number of countries ( 17 , 23 , 24 ) and in some healthcare systems patients are payers in addition to being the focal point of what healthcare is about. As payers, patients are legitimate stakeholders within HTA.…”
Section: Involving Patients In Htamentioning
confidence: 99%
“…Co-creation with patients can add to the legitimacy of the HTA process for the common good (14). Currently patient involvement is limited in its scope and barriers to their involvement include the lack of information to patients and public about HTA and the lack of policies (15)(16)(17), and the need for culture change (18)(19)(20)(21). The "invited spaces" for patient participation have been set by HTA policy and practice and leave significant opportunities for broadening through mutual discussions (22).…”
Section: Involving Patients In Htamentioning
confidence: 99%
“…In the first phase, Silva (10) showed the gradual implementation of PPI actions by the Brazilian HTA agency. However, like many other HTA bodies, the strategies do not go beyond consultation level (22). Considering the current trend to broaden the spectrum of involvement to increase genuine participation (6) and the findings from this study, the involvement strategies already used in Brazil should be expanded, for an earlier, more direct, and active participation.…”
Section: Discussionmentioning
confidence: 87%
“…First, PPI in healthcare innovation has taken a number of approaches, and the majority of the studies reviewed focused on process and service innovation ( n = 62, 71%), while only seven studies (8%) focused on technological innovation and five (6%) on systems innovation. In terms of technological innovation, this trend is reflected in Gagnon et al's 103 review of PPI in health technology assessment, where the use of PPI in the development of technology is recognized as a relatively recent growth area. Second, the studies reviewed focused on PPI in earlier stages of the innovation journey in comparison to later stages, reflecting PPI trends in general 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Caution and ambivalence towards the use of PPI in health technology development have long been noted 106 . Recently, it was identified that the use of PPI is increasing in this area of innovation; however, challenges continue, including lack of public knowledge/awareness and lack of guidance on how to use PPI in health technology innovation 103 . It has been suggested that the slow take‐up of PPI in this field of innovation is due to the dual roles of the health technology community to contribute to both research and policy‐making 107 .…”
Section: Discussionmentioning
confidence: 99%